Multifaceted Challenges Encountered by English for Specific Purposes (ESP) Lecturers in the Context of Pedagogical Instruction: A Comprehensive Case Study - Nasution, Dina Syarifah; Syarif, Hermawati; Zainil, Yetti (Universitas Pahlawan Tuanku Tambusai, 2023)
This comprehensive case study investigates the multifaceted challenges faced by English for Specific Purposes (ESP) lecturers in the context of pedagogical instruction at STAIN Madina, Indonesia. ESP instruction is crucial for equipping students with specialized language skills tailored to their future careers. However, this research reveals various challenges ESP lecturers encounter, including curriculum design complexities, pedagogical strategy adaptations, resource limitations, diverse student backgrounds, and assessment intricacies. These challenges impact the quality of ESP instruction, with implications for student preparedness in religious studies and beyond. The significance of this study lies in its potential to enhance the overall quality of ESP education at STAIN Madina and similar institutions in Indonesia and globally. Practical recommendations are provided for addressing these challenges, such as curriculum updates, innovative teaching strategies, improved resources, tailored support for diverse student backgrounds, and alternative assessment methods. By understanding and mitigating these challenges, institutions can better prepare students for specialized careers, fostering effective communication in various professional domains